Analysis of emulsion fuel spray characteristics using SAC and VCO nozzle - Che Hanisah, Yaacob (2012)
The presence of water within diesel fuel in the form of water-in-diesel (W/D) emulsion lowers the pollution level of nitrogen oxides and particulate matter. The spray penetration and spray angle is the basic phenomenon that can show the combustion inside the chamber where it can determine the time taken for complete combustion. The influences of injector nozzle geometry, injection pressure and ambient air conditions on emulsion fuel spray were examined using simulation ANSYS CFD Fluent 12.1. The emulsion fuel is carried on of 5%, 10% and 15% of water being analyzed at single hole nozzle, 0.2mm on different injection pressure, 0.4MPa and 1.3MPa. This simulation also had been analyzed on different nozzle, SAC and VCO nozzle. The spray penetration showed the differences for both injection pressure, where the highest injection pressure produced the furthest spray penetration compared to the lowest of injection pressure. 5% of water gave the furthest spray penetration due to the emulsion properties of viscosity, where it has highest viscosity compared to the 10% and 15% of water. Comparison were made between different nozzle geometries while the SAC nozzle resulted in furthest spray penetration due to the design and geometry compared to the VCO nozzle under the same conditions.